Bioleaching of valuable metals Li, Co, Ni and Mn from spent electric vehicle Li-ion batteries for the purpose of recovery. (10th March 2016) - Xin, Yayun; Guo, Xingming; Chen, Shi; Wang, Jing; Wu, Feng; Xin, Baoping
Abstract: Swift development of electric vehicle (EV) absolutely produces enormous amounts of spent EV Li-ion batteries (LIBs), hence more studies should be performed to seek cheap, efficient, safe and eco-friendly ways for the recovery of spent EV LIBs. In this work, release of valuable Li, Co, Mn and Ni from three typical spent EV LIBs cathode LiFePO4, LiMn2 O4 and LiNix Coy Mn1-x-y O2 by bioleaching at 1% pulp density was explored for the first time. The results showed the maximum extraction efficiency of Li occurred in the sulfur– At system, indicating that Li release was due to acid solution by biogenic H2 SO4 ; whereas the mixed energy source-mixed culture system harvested the highest dissolution yield for Co, Ni and Mn than other systems, suggesting these metals were mobilized by a combined work of Fe 2+ reduction and acid dissolution. Moreover, a non-contact mechanism accounted for Li extraction, while a contact mechanism between the cathodes and cells was essential for mobilization of Co, Ni and Mn. Due to the enhancement effect in cell growth, pH adjustment greatly improved bioleaching performance, an average extraction efficiency of 4 valuable metals from the resistant LiNix Coy Mn1−x−y O2 reached more than 95%, especially the release efficiencies of Co and Ni rose from 43.5% to 96% and from 38.3% to 97%, respectively. The rather high extraction efficiencies of the valuable metals suggest that the cheap autotrophic bioleaching is capable of recovery of the spent EV LIBs. Highlights: Bioleaching efficiently released Li and Mn from EV LIBs, but poor with Co and Ni. pH adjustment evidently improved bioleaching performance, especially Co and Ni. Li release was due to solution by biogenic H2 SO4 based on indirect mechanism. Release of Co, Mn, Ni was due to co-work of Fe 2+ reduction and acid dissolution. Direct contact between cathodes and cells was needed for release of Co, Ni and Mn.